Increased Nociceptive Responses in Streptozotocin-Induced Diabetic Rats and the Related Expression of Spinal NR2B Subunit of N-Methyl-D-Aspartate Receptors - Ismail, Che Aishah Nazariah; Suppian, Rapeah; Aziz, Che Badariah Abd; Haris, Khalilah; Long, Idris (Korean Diabetes Association, 2019)
Background: This study investigated the role of NR2B in a modulated pain process in the painful diabetic neuropathy (PDN) rat using various pain stimuli. Methods: Thirty-two Sprague-Dawley male rats were randomly allocated into four groups (n=8): control, diabetes mellitus (DM) rats and diabetic rats treated with ifenprodil at a lower dose (0.5 μg/day) (I 0.5) or higher dose (1.0 μg/day) (I 1.0). DM was induced by a single injection of streptozotocin at 60 mg/kg on day 0 of experimentation. Diabetic status was assessed on day 3 of the experimentation. The responses on both tactile and thermal stimuli were assessed on day 0 (baseline), day 14 (pre-intervention), and day 22 (post-intervention). Ifenprodil was given intrathecally for 7 days from day 15 until day 21. On day 23, 5% formalin was injected into the rats’ hind paw and the nociceptive responses were recorded for 1 hour. The rats were sacrificed 72 hours post-formalin injection and an analysis of the spinal NR2B expression was performed. Results: DM rats showed a significant reduction in pain threshold in response to the tactile and thermal stimuli and higher nociceptive response during the formalin test accompanied by the higher expression of phosphorylated spinal NR2B in both sides of the spinal cord. Ifenprodil treatment for both doses showed anti-allodynic and anti-nociceptive effects with lower expression of phosphorylated and total spinal NR2B. Conclusion: We suggest that the pain process in the streptozotocin-induced diabetic rat that has been modulated is associated with the higher phosphorylation of the spinal NR2B expression in the development of PDN, which is similar to other models of neuropathic rats.